Do Teacher Questions Function as Assessment for Learning? - Hieronimus Canggung Darong; Erna Mena Niman (RIRAI Publisher, 2021)
This study wants to challenge the robust idea of previous findings revealing that employing a particular question type would necessarily functions as Assessment for Learning (AfL). Besides, this study extends previous research focusing on typology and examines the syntactical forms of questioning in its practice. To gather data, six Indonesian English teachers were observed and audio- recorded, thus, transcribed and analysed following the principle of Conversation Analysis (CA). Except referential type functioning as a teaching technique and a discourse marker choice to discursively extend the classroom talk, the result of analysis corroborates previous studies in that they provide diagnostic information from which a better further action was taken place as highlighted in the AfL. Yet, this might occur as questioning types are syntactically constructed following classroom discourse moves. Thus, the examination of questionings functioning as Assessment for Learning (AfL), aside from types, the syntactical form and classroom discourse moves are important to cope with.